Use of serious games with older adults: systematic literature review - Bárbara-Mariana Gutiérrez-Pérez; Antonio-Víctor Martín-García; Alicia Murciano-Hueso; Ana-Paula de Oliveira Cardoso (Humanities & Social Sciences Communications, 2023)
Abstract The aim of this paper is to qualitatively synthesise literature on empirical research into video games and older adults. A total of 108 studies were analysed, with the participation of 15,902 individuals aged over 60. The framework of Search, Appraisal, Synthesis, and Analysis (SALSA) was used, with screening by three independent reviewers and phrase searching and combining search terms. The results indicate a majority of studies with a quantitative approach conducted in the European context in which a total of 125 scales were identified for the assessment of different geriatric aspects related to domains for the improvement of physical health and functional quality, improvement of cognitive, psychological and mental health, and improvement of physical and cognitive functions from a combined approach.